Policy comparison of lead hunting ammunition bans and voluntary nonlead programs for California condors - John H. Schulz; Samantha Totoni; Sonja A. Wilhelm Stanis; Christine Jie Li; Mark Morgan; Damon M. Hall; Elisabeth B. Webb; Robin M. Rotman (Wildlife Society Bulletin, 2023)
Abstract The endangered California condor (Gymnogyps californianus) is negatively affected by lead poisoning from spent lead‐based hunting ammunition. Because lead poisoning is the primary mortality factor affecting condors, the California Fish and Game Commission banned lead hunting ammunition during 2008 in the southern California condor range followed by a statewide ban implemented in 2019. In contrast, the Arizona Game and Fish Department instituted an outreach and awareness program encouraging voluntary use of nonlead hunting ammunition in the northern portion of the state during 2005 and a similar program was launched in Utah during 2012. The juxtaposition of policy tools provided a unique opportunity to evaluate the intended efforts to mitigate lead exposure in condors and their respective positive and negative effects. Herein we reflect upon the effectiveness of lead policy actions in the 3‐state region on the basis of condor blood‐lead levels, population status, and hunter awareness of the issue and use of nonlead hunting ammunition.